Analisis People, Process dan Physical Evidence Terhadap Keputusan Pembelian Produk Telekomunikasi di Medan - Ramadhan Harahap; Surya Asih (Jurnal AKMAMI (Akuntansi Manajemen Ekonomi), 2021)
This study aims to determine whether the leadership style and organizational culture influence employee motivation at Sampali Asri PT Kurnia Medan. This research using descriptive data analysis, multiple regression analysis with t-test (test partial), F test (simultaneous test) and test the coefficient of determination (R2). This research test equipment using multiple linear regression model. The conclusion that can be drawn from the test results, the stimulatory and partial leadership style and organizational culture influence employee motivation